Mediating Effect of Safety Climate on Occupational Safety Management and Employee Performance - Sunil Kumar NG; Pinakapani Peri; Thirupathi Chellapali (The Indonesian Journal of Occupational Safety and Health, 2025)
Introduction: Occupational Safety Management (OSM) is crucial for workplace safety, especially in high-risk industries. While a positive Safety Climate (SC) promotes safe behavior and boosts Employee Performance (EP), its mediating role between OSM and EP remains underexplored in the FMCG sector. This study investigates how SC mediates the relationship between OSM and EP in FMCG manufacturing industries in Bagmati Province, Nepal. Research Objective: To examine the mediating role of the Safety Climate in the relationship between Occupational Safety Management and Employee Performance in FMCG manufacturing industries in Bagmati Province, Nepal. Methods: This mixed-method study combines quantitative surveys and qualitative interviews, collecting data from 460 FMCG manufacturing employees. A 5-point Likert scale measured OSM, Safety Climate, and EP. Structural Equation modeling (SEM) using AMOS and SPSS tested relationships and mediation effects. Reliability was confirmed with a Cronbach’s Alpha of 0.875. Results: Structural Equation Modelling showed that OSM positively impacts Safety Climate (β=0.76), which in turn enhances EP (β=0.37). OSM also directly influences EP (β=0.47). The mediating role of the Safety Climate was confirmed (indirect effect β=0.277, p=0.000) and validated using the bootstrap method (5,000 samples). Conclusion: The study confirms that Safety Climate significantly mediates the relationship between OSM and EP. Enhancing the Safety Climate through leadership, engagement, and training can boost performance. The findings offer valuable insights for improving safety and productivity in the FMCG sector.